Development of functional hydroxyethyl cellulose-based composite films for food packaging applications - Zhang, Xueqin; Guo, Haoqi; Luo, Wenhan; Chen, Guojian; Xiao, Naiyu; Xiao, Gengsheng; Liu, Chuanfu (Frontiers in Bioengineering and Biotechnology, 2022)
Cellulose-based functional composite films can be a good substitute for conventional plastic packaging to ensure food safety. In this study, the semi-transparent, mechanical strengthened, UV-shielding, antibacterial and biocompatible films were developed from hydroxyethyl cellulose (HEC). Polyvinyl alcohol (PVA) and ε-polylysine (ε-PL) were respectively used as reinforcing agent and antibacterial agent, and chemical cross-linking among these three components were constructed using epichlorohydrin (ECH). The maximum tensile strength and elongation at break were 95.9 ± 4.1 MPa and 148.8 ± 2.6%, respectively. TG-FTIR and XRD analyses indicated that chemical structure of the composite films could be well controlled by varying component proportion. From UV-Vis analysis, the optimum values of the percentage of blocking from UV-A and UV-B and UPF values were 98.35%, 99.99% and 60.25, respectively. Additionally, the composite films exhibited good water vapor permeability, swelling behavior, antibacterial activity and biocompatibility. In terms of these properties, the shelf life of grapes could be extended to 6 days after packing with the composite film.